Improving the Brake Control Effectiveness of Vehicles Equipped with a Pneumatic Brake Actuator - V. Bogomolov; V. Klimenko; L. Leontiev; L. Ryzhyh; O. Smyrnov; M. Kholodov (Наука и техника)
This paper proposes a way to determine a rational connection between a two-section or three-section brake valve and the main brake system circuits of a wheeled vehicle equipped with simplex or duo-duplex brake gears. The aim is to determine a rational option to connect main brake system circuits with a brake valve to guarantee the maximum effectiveness of an emergency brake system if any device of the brake actuator of a multiaxle wheeled vehicle is out of order, using the methods of combinatorics. The feature of the proposed way, determining the rational connection of a brake valve with the main brake system circuits of a multiaxle wheeled vehicle, is the application of combinatorics methods, taking into account the features of a brake valve design. New mathematical interconnections between the quantities of the connection points of circuits and simplex and duo-duplex brake gears enable us to determine the rational scheme of the application of the brake gear circuits of a multiaxle wheeled vehicle. Mathematical expressions that enable us to compute the number of possible connection points of two-section and three-section brake gears and simplex and duo-duplex brake gears, which are installed on the axles of a multiaxle wheeled vehicle, have been determined. It is proposed to use a universal mathematical dependence to determine the number of rational options to connect the brake actuator circuits of a multiaxle wheeled vehicle. The diagram of the calculated scheme of the connection between circuits and the two-section or three-section brake valve of simplex or duo-duplex brake gears is presented. It simplifies the determination of the number of rational options to connect brake actuator circuits with the brake gears and brake valve of a multiaxle wheeled vehicle. In review the analysis of requirements to be fulfilled in accordance with international standards is provided and the evaluation of the effectiveness of the emergency brake system of some wheeled vehicles is carried out. The general concept to determine the rational layout of the emergency brake system of a multiaxle wheeled vehicle on the basis of the arrangement schemes of the connection between two-section or three-section brake valves and simplex and duo-duplex brake gears is proposed.